Density Functional Theory:A Powerful Tolls for Solving the Many Body Problem - Ali Hussain Reshak (Penerbit Universiti Malaysia Perlis, 2014)
The purpose of this book is to give an idea about using the Density Functional Theory (DFT) for solving many body problems.